CHARACTERISTICS OF PATIENTS WITH GONORRHEA AND SYPHILIS TREATED AT THE CITY INSTITUTE FOR SKIN AND VENEREAL DISEASES IN BELGRADE IN 2016 AND 2024 - Bjekić, Milan (HEALTH CARE, 2025)
Introduction/Aim: Gonorrhea and syphilis are common bacterial sexually transmitted infections, with a continuous increase being recorded worldwide. This rise is explained by the increase in risky sexual behaviors, meeting sexual partners through mobile applications, engaging in chemsex, as well as more frequent testing for these sexually transmitted infections among vulnerable groups. The aim of this study was to determine whether there are differences in the characteristics of patients with gonorrhea and syphilis treated at the City Institute for Skin and Venereal Diseases in Belgrade during 2016 and 2024, and to identify factors that influence the current epidemiological situation related to gonorrhea and syphilis.Methods: Data on basic demographic characteristics, sexual orientation, HIV status, and history of previous sexually transmitted infections among patients with gonorrhea and syphilis were collected from electronic medical records and partner notification forms of individuals diagnosed with these infections. The statistical analysis of the data was performed using the χ² test and Student's t-test.Results: Patients diagnosed with gonorrhea in 2024, compared to those diagnosed in 2016, were significantly more often male (p
Keywords: gonorrhea, syphilis, demographic characteristics, diagnosis, treatment, sexual orientation